Eating Behavior of Indonesian Adults Differs by Metropolization Levels based on the 2018 Indonesian Food Barometer - Febriana, Nor Laila; Februhartanty, Judhiastuty; Hanisa, Nisrina; Khusun, Helda (Universitas Airlangga, 2024)
Modernization leads to nutrition transition process, shifts eating behavior into a more modernized pattern that may increase the risk of non-communicable diseases (NCDs). Using the 2018 Indonesian Food Barometer (IFB) data, this study assessed the differences in eating behavior between metropolization levels among Indonesian adults. 1482 adults aged 18-64 in six provinces were involved. Eating behavior was defined by the number of eating events, food preparation, eating location, eating companion, and activity while eating. Metropolization level was defined based on the gross domestic regional product (GRDP), GRDP/capita, population size, population density, and non-agricultural worker proportion. Differences in each eating behavior dimension between metropolization levels were analyzed using the Chi-square test (p<0.05) and adjusted with sociodemographic factors using logistics regression. 83.9% of the subjects had â‰¤5 eating events/day and dominated by 4-5 eating events/day. 51.2% and 83.1% of the subjects cooked and ate at home frequently, indicating the practice of traditional eating. Meanwhile, the tendency towards modern dimension can be seen as the proportion of eating alone frequently and eating only less frequently were 60.3% and 67.9%, respectively. Eating behavior differed significantly (p<0.05) between metropolization levels, except for eating with company. Proportion of not cooking and eating away from home frequently increase as metropolization level increases (p<0.05) after adjusted with sociodemographic factors while eating alone and eating only showed no significant differences. Modern eating behavior tendency increases along with metropolization level. Improving living and working conditions in metropolitan areas is imperative to facilitate healthier eating behavior among the inhabitants.